PENGALAMAN BERSUA TUHAN: Prespektif William James dan al-Ghazali - Komarudin, Komarudin (WALISONGO, 2012)
Abstract Experience of meeting God constitutes an interresting phenomenon and become the focus of interrest of many disciplines. Psychology and tasawuf are two disciplines which focusedly study this phenomenon applying different approaches. Ghazali is the representative of the dicsipline of tasawwuf and William James is the representative of the dicsipline of psychology. The both experts applied the different approaches in studying the religious experiences. Epistemological base on which William James used , has the scientific accountability but less accurate in the source of knowledge. In other side, Ghazali has a deep source of knowledge but less of rationality. An effort to compromise the both approach in order to study about the experience of meeting God will result in a comprehensive, deep, and objective depiction. *** Pengalaman bersua Tuhan merupakan fenomena yang menarik dan menjadi titik perhatian banyak disiplin ilmu. Psikologi dan tasawuf merupakan dua disiplin ilmu yang memfokuskan kajiannya pada fenomena ini dengan menerapkan pendekatan yang berbeda. Ghazali adalah representasi dari disiplin ilmu tasawuf dan William James adalah representasi disiplin ilmu psikologi. Kedua ahli tersebut menggunakan pendekatan yang berbeda dalam mengkaji pengalaman keagamaan. Basis epistimologi yang digunakan oleh James memiliki akuntabilitas ilmiah namun kurang akurat dalam sumber pengetahuannya. Di sisi lain Ghazali memiliki sumber pengetahuan yang dalam namun kurang dari sisi rasionalitas. Upaya untuk mengkompromikan kedua pendekatan dalam rangka untuk mengkaji pengalaman bersua Tuhan akan menghasilkan penggambaran yang dalam dan obyektif. Keywords: pengalaman religius, maârifat, psikologi, tasawuf BIBLIOGRAFI Ali, Yunasril, Manusia Citra Ilahi, Jakarta: Paramadina, 1997. Ansari, Muhammad Abd. Haq, Merajut Tradisi Syari`ah dengan Sufisme, terj. Achmad Nashir Budiman, Jakarta: Grafindo Persada, 1997. Arberry, A.J., Sufism: An Account of the Mystics of Islam (Pasang Surut Aliran Tasawuf), terj. Bambang Herawan, Bandung: Mizan, 1989. Azhari, Noer, Kautsar, Ibn al-âArabi Wahdat al-Wujud dalam Perdebatan, Jakarta: Paramadina, 1995. Atkinson, et.all., Pengantar Psikologi jilid 1-2, terj. Dra. Nurdjannah Taufiq, Jakarta: Erlangga, 1993. Bakar, Osman, Hierarkhi Ilmu Membangun Rangka-Pikir Islamisasi Ilmu, terj. Purwanto, Bandung: Mizan, 1997. Chittick, William C., The Sufi Path of Knowledge, terj. Ahmad Nidjam, M.Sadat Ismail. Dan Ruslani, Yogyakarta: Qalam, 2001. Devidoff, Linda L., Psikologi Suatu Pengantar, Jakarta: Erlangga, 1988. al-Faruqi, Ismaâil Raji, Tauhid, terj. Rahmani Astuti, Bandung: Pustaka, 1982. Fathurahman, Oman, Menyoal Wahdatul Wujud Kasus Abdurrauf Singkel di Aceh Abad 17, Bandung: Mizan, 1999. Gazur-i-Ilahi, Shayk Ibrahim, Mengungkap Misteri Sufi Besar Mansur al-Hallaj âAna âl-á¸¥aqq,â terj. Hr. Bandaharo dan Joebaar Ajoeb, Jakarta: Raja Grafindo Persada, 2000. Ghazali, MiskÄt al-AnwÄr (Miskat Cahaya-cahaya), terj. Muhammad Bagir, Bandung: Mizan, 1992. __________, Iá¸¥yÄâ âUlÅ«m al-DÄ«n, Indonesia: Dar Ihya al-Kutub al-âArabiyah, t.th. __________, al-Munqid min âl-á¸alÄl, Beirut: Dar al-Fikr, 1996. __________, al-Tibr al-MasbÅ«q fi Naá¹£Äih al-Muluk, Riyad: Dar al-Azariyah, 1994. __________, MajmÅ« RasÄâil, Beirut: Dar al-Fikr, 1996. __________, Kimiya al-SaâÄdah, Beirut: al-Maktabah al-Syabiyah, t.th. __________, al-QawÄâid al-âAshrah, Beirut: al-Maktabah al-Syabiyah, t.th. Hallaj, al-Husain ibn Manshur, al-Thawwasin, Paris: t.p., 1913. Hidayat, Komaruddin dan Muhammad Wahyuni Nafis, Agama Masa Depan Perspektif Filsafat Perenial, Jakarta: Paramadina, 1995. Hidayat, Komaruddin, Memahami Bahasa Agama Sebuah Kajian Hermeneutik, Jakarta: Paramadina, 1996. Hujwiri, âAli âUtsman, Kasyf al-Mahjub, terj. Suwardjo Muthary dan Abdul Hadi W.M., Bandung: Mizan, 1993. Iqbal, Muhammad, The Reconstruction of Religious in Islam (Pembangunan Kembali Alam Pikiran Islam), terj. Osman Raliby, Jakarta: Bulan Bintang, 1883. Izutsu, Toshihiko, Relasi Tuhan dan Manusia, terj. Agus Fahri Husein, Supriyanto Abdullah, dan Amirudin, Yogyakarta: Tiara Wacana, 1997. James, William, The Varieties of Religious Experience, terj. Gunawan Admiranto, Bandung: Mizan, 2004. __________, The Will to Believe and Human Immortality, New York and Chicago: Bob Corbett, 1987. __________, Pragmatism: and Four Essays from The Meaning of Truth, New York: Meridian Books, 1959. Kalabadzi, ibn Abi Ishaq Muhammad ibn Ibrahim, al-TaâÄruf li Madhhab Ahl al-Taá¹£awwuf (Ajaran Kaum Sufi), terj. Rahmani Astuti, Bandung: Mizan, 1995. Khaja Khan, Khan Sahib, Tasawuf Apa dan Bagaimana, terj. Achmad Nasir Budiman, Jakarta: RajaGrafindo Persada, 1995. King, Richard, Orientalism and Religion Postcolonial Theory, India and âthe Mystic Eastâ (Agama, Orientalisme, dan Poskolonialisme), terj. Agung Prihantoro, Yogyakarta: Qalam, 2001. Madjid, Nurcholish, et.all, Kontektualisasi Doktrin Islam dalam Sejarah, Jakarta: Paramadina, 1995. Massignon, Louis, Al-Hallaj Sang Sufi Syahid, terj. Dewi Candraningrum, Yogyakarta: Fajar Pustaka Baru, 2001. Masyhur, Kahar, Meninjau Berbagai Ajaran, Jakarta: Kalam Mulia, 1986. Mubarak, Zaki, at-Tasawwuful Islami fi Adab wa Akhlaq, Jil. II, Mesir: t.p., 1938. Muhammad, Hasyim, Dialog antara Tasawuf dan Psikologi, Yogyakarta: Pustaka Pelajar, 2002. Murata, Sachiko, The Tao of Islam, terj. Rahmani Astuti dan M.S. Nasrullah, cet. ke- 2, Bandung: Mizan, 1997. Nasr, Seyyed Hossein, Intelektual Islam Teologi Filsafat dan Gnosis, terj. Suharsono dan Jamaluddin MZ, Yogyakarta: CIIS, 1995. __________, Knowledge and the Secred (Pengetahuan dan Kesucian), terj. Suharsono, Yoryakarta: Pustaka Pelajar, 1997. __________, Islamic Art and Spirituality (Spiritualitas dan Seni Islami), terj. Drs. Sutejo, Bandung: Mizan, 1993. Nata, Abuddin, Metodologi Studi Isla m, Jakarta: Raja Grafindo Persada, 2001. Nawawi, Hadari, Hakekat Manusia Menurut Islam, Surabaya: al-Ikhlas, 1993. Pals, Daniel L., Seven Theories of Religion, terj. Ali Noer Zaman, Yogyakarta: Qalam, 2001. Sadra, Mulla, Kearifan Puncak, terj. Dr.Ir. Dimitri Mahayana dan Ir. Dedi Djunardi, Yogyakarta: Pustaka Pelajar, 2001 Sagiran, Mukjizat Gerakan Shalat, Jakarta Selatan: Qultummedia, 2007 Schimmel, Annemarie, Dimensi Mistik Dalam Islam, Yogyakarta: Pustaka Firdaus, 2000. Schoun, Frithjof, Sufism: Veil & Quintenssence (Tasawuf Prosesi Ritual Menyingkap Tabir Mencari Yang Inti), terj. Tri Wahono Budhi Santoso, Jakarta: Raja Grafindo Persada, 2000. Soedjarwo, Djaâfar, al-Janibul Illahi, Aspek Ketuhanan Sebagian dari Rasional Islam, Surabaya: al-Ikhlas, 1993. Stevenson, Leslie dan David L. Haberman, Ten Theories of Human Nature (Sepuluh Teori Hakekat Manusia), terj. Yudi Santoso dan Saut Pasaribu, Yogyakarta: Yayasan Bentang Budaya, 2001 Taftazani, Abu al-Wafaâ al-Ghanimi, Sufi dari Zaman ke Zaman, terj. Ahmad Rofiâ Utsmani, Bandung: Pustaka,1985. Tholuck, Priedrich August Deofidus, Sufisme sive Theosophia Persarum Pantheistica, Berlin: t.p.,1921. Yazdi, Mehdi Haâiri, Ilmu Huá¸uri, terj. Ahsin Mohammad, Bandung: Mizan, 1992. Walgito, Bimo, Pengantar Psikologi Umum, Yogyakarta: Andi, 2002. Wilcox, Lynn, Sufism and Psychology (Psychosufi), terj. Soffa Ihsan, Jakarta: Pustaka Cendekia Muda, 2007. Wirawan, Sarlito, Pengantar Umum Psikologi, Jakarta: Bulan Bintang, 1982.